Revisiting Fat Graft Harvesting and Processing Technique to Optimize Its Regenerative Potential - Karina Karina, MD, PhD; Johannes A. Biben, MD; Krista Ekaputri, MD; Grady Krisandi, BMed; Imam Rosadi, MSc; Siti Sobariah, BSc; Irsyah Afini, MBiomed; Tias Widyastuti, BSc; Alfida Zakiyah, BSc; Difky Ernanda, BSc (Plastic and Reconstructive Surgery, Global Open)
Background:. The use of fat grafting has expanded to include cell and tissue regeneration, necessitating investigations to ensure the viability of stromal and adipose-derived mesenchymal stem cells (ASCs) within the transferred fat parcels. This study explored the impact of harvesting technique and centrifugation on the viability of stromal cells and ASCs in lipoaspirate. Methods:. Fat was harvested from patients undergoing fat grafting using 2 types of liposuction cannula: (A) a 3-mm blunt tip cannula with 3 smooth holes and (B) a 2.4-mm, sharp point port, multihole blunt tip cannula. Fat from cannula B underwent different processing methods: no centrifugation, 300g, 600g, and 900g centrifugation. Stromal cells were isolated, quantified, and evaluated for viability. ASCs were cultured from these samples to confirm survival. Results:. Lipoaspirates from 21 patients were analyzed. The mean stromal cell counts were 0.937 × 109 ± 0.346 × 109/mL for cannula A and 0.734 × 109 ± 0.266 × 109/mL for cannula B (P = 0.684), with viabilities of 98.79% and 98.22% (P = 0.631), respectively. ASCs isolated and after 2-passage culture were also higher for cannula A. Stromal cell quantification and viability were lowest in the noncentrifuged group (P < 0.05) and highest in the 600g centrifugation group. Conclusions:. Fat harvesting using cannulas A and B showed no significant difference in stromal cell yield or viability. Handheld syringe liposuction preserved stromal vascular fraction cell and ASC viability. Centrifugation at different speeds did not significantly affect stromal cell viability.